IMPLEMENTASI PELAKSANAAN BIMBINGAN DAN KONSELING DI MASA PANDEMI COVID-19: A LITERATURE REVIEW - Intan Prawitasari (Syi’ar: Jurnal Ilmu Komunikasi, Penyuluhan dan Bimbingan Masyarakat Islam, 2020)
Corona virus is defined by WHO as a global pandemic, which has a tremendous impact on human life. One of the impacts as a result of the COVID-19 pandemic in the field of education is distance learning. Distance learning is learning that is carried out through online media as a substitute for face-toface at school. Distance learning has changed the educational setting, having an effect not only on the teach and learn process but also on the guidance and counseling services in school. With the COVID-19 pandemic, it becomes a new challenge for guidance and counseling teachers in providing services and carrying out their duties as school counselors. The purpose of this study is for describing the implementation of guidance and counseling during the COVID-19 pandemic and providing an overview and understanding to several groups. The research method used is the library appoarch. As for data collections tecniques used the documentation method in the form of scientific journals published in national and international on the internet. While the study of data analysis applied was the content analysis technique. Results of search and research are, 1) the implementation of guidance and counseling services in the COVID-19 pandemic, 2) the duties and characteristics of counselors needed during the COVID-19 pandemic.